EPIDEMIOLOGIC STUDY OF CONFIRMED CASES OF LEISHMANIASIS IN HUMANS INTHE AREIA CITY – PARAÍBA BETWEEN 2010 AND 2011 (Fiep Bulletin - online, 2014)
Leishmaniasis constitutes a public health problem due to the incidence, the wide geographical distribution and the presence of disfiguring sequels, destructive and disabling the disease provokes in the man, especially in populations of poorer areas and with precarious basic sanitation. Considering the endemic potential of the city Areia - Paraiba for leishmaniasis, the study had as objective to do a rising of leishmaniasis cases confirmed in the city between the years 2010 and 2011. The data were collected through the information database from the SUS Department of Informatics (DATASUS) and medical records and notifications books donated by Health Department in Areia – PB. After identification of the bearers, they were visited for applying a qualitative questionnaire for verification of the information demographic and epidemiological which are submitted to the population in study. Was notified thirteen (13) cases of leishmaniasis, only for the cutaneous form of the disease (ACL), being the year of 2010 the period of larger notification registered representativeness of ten (10 ) cases positivized and 2011 with three (03) registered cases of the pathology, with a decline around 53,84%, in the respective time interval. A percentage of 15,38% of the notifications arrived to death and 84,61% obtained the regression and cicatrization of the ulcers. The distribution of the disease population zone showed reasonably homogeneous, with a proportion of 53,84% for the urban and 46,15% for the rural. The disease manifested most frequently in the men (69,23%) than in the women (30,76%) where the population interviewee presented very low education degree (46,15%) of illiterates; was also verified a considerable agglomerate of people added to the existence of domestic dogs, precarious houses near or inserted in the woods, with sanitary spilling to open sky or sewage box.
Keywords: Leishmaniose; compulsory notification; epidemiology.